Deregulation of Annexin-A1 and Galectin-1 Expression in Precancerous Gastric Lesions: Intestinal Metaplasia and Gastric Ulcer - Ana Flávia Teixeira Rossi; Márcia Cristina Duarte; Ayla Blanco Poltronieri; Marina Curado Valsechi; Yvana Cristina Jorge; Dalísio de-Santi Neto; Paula Rahal; Sonia Maria Oliani; Ana Elizabete Silva (Mediators of Inflammation)
Objective. Annexin-A1 (ANXA1/AnxA1) and galectin-1 (LGALS1/Gal-1) are mediators that play an important role in the inflammatory response and are also associated with carcinogenesis. We investigated mRNA and protein expression in precancerous gastric lesions that participate in the progression cascade to gastric cancer, such as intestinal metaplasia (IM) and gastric ulcer (GU). Methods. Quantitative real-time PCR (qPCR) and immunohistochemical techniques were used to analyze the relative quantification levels (RQ) of ANXA1 and LGALS1 mRNA and protein expression, respectively. Results. Increased relative expression levels of ANXA1 were found in 100% of cases, both in IM (mean RQ=6.22±0.06) and in GU (mean RQ=6.69±0.10). However, the LGALS1 presented basal expression in both groups (IM: mean RQ=0.35±0.07; GU: mean RQ=0.69±0.09). Immunohistochemistry revealed significant positive staining for both the AnxA1 and Gal-1 proteins in the epithelial nucleus and cytoplasm as well as in the stroma of the IM and GU groups (P<0.05) but absence or low immunorectivity in normal mucosa. Conclusion. Our results bring an important contribution by evidencing that both the AnxA1 and Gal-1 anti-inflammatory proteins are deregulated in precancerous gastric lesions, suggesting their involvement in the early stages of gastric carcinogenesis, possibly due to an inflammatory process in the gastric mucosa.